2022
DOI: 10.1021/acsmaterialslett.2c00306
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Anchoring Effect of MXene-Supported Single Atoms as Cathodes for Aluminum–Sulfur Batteries

Abstract: As an alternative energy storage system, the stable cycle and high-rate performance of aluminum–sulfur (Al–S) batteries are increasingly affected by the dissolution of intermediate Al polysulfide (Al2S n ) into the electrolyte. Introducing anchoring materials that can promote Al2S n conversion is an effective way to solve this problem. However, the lack of an interaction mechanism between Al2S n and anchoring materials hinders the design of anchoring materials. Here, we used single-atom-loaded MXene (SA@MXen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…As far as we know, all reports about Ca-S cells have exploited simple sulfur–carbon composites at the positive side by applying mesoporous carbon materials . On the contrary, in the case of Al-S systems, where the shuttle effect of PS is remarkable, the majority of publications have exploited sulfur host structures based, for example, on activated carbon, MOFs, M-Xenes, and doped graphene . Ai et al developed a TiN@N-doped graphene catalyst for use as the sulfur cathode in Al-S batteries, which suppressed the Al-PS shuttle effect, improved the redox kinetics, and reduced the decomposition barrier, being able to deliver ∼993 mAh g –1 in the first cycle and to maintain a capacity of ∼500 mAh g –1 after 200 cycles (see Figure e) .…”
Section: Challenges For the Development Of A Reliable Positive Electr...mentioning
confidence: 99%
See 3 more Smart Citations
“…As far as we know, all reports about Ca-S cells have exploited simple sulfur–carbon composites at the positive side by applying mesoporous carbon materials . On the contrary, in the case of Al-S systems, where the shuttle effect of PS is remarkable, the majority of publications have exploited sulfur host structures based, for example, on activated carbon, MOFs, M-Xenes, and doped graphene . Ai et al developed a TiN@N-doped graphene catalyst for use as the sulfur cathode in Al-S batteries, which suppressed the Al-PS shuttle effect, improved the redox kinetics, and reduced the decomposition barrier, being able to deliver ∼993 mAh g –1 in the first cycle and to maintain a capacity of ∼500 mAh g –1 after 200 cycles (see Figure e) .…”
Section: Challenges For the Development Of A Reliable Positive Electr...mentioning
confidence: 99%
“…On the computational side, an extensive DFT study was carried out by Wang et al in order to unravel the anchoring properties of SAC-decorated (SA@Ti 3 C 2 O 2 ) M-Xenes by screening several SAC metals. Their analysis showed that SAC = Y, Nb, Mo, and Tc are potential candidates for high-performance cathodes, showing good adsorption energies for Al-PS and low reaction barriers (see Figure e) …”
Section: Challenges For the Development Of A Reliable Positive Electr...mentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, elemental sulfur with high specific capacity (1672 mAh g −1 ) and low cost is a promising cathode material for high-energy-density AMBs, that is, Al-S batteries. [11][12][13][14][15][16] When the sulfur cathode is dis-/charged in a potential window <1.8 V versus Al 3+ / Al with the [AlCl 3 ] 1.3 [EmimCl] 1 electrolyte, the reaction mechanism can be described by the following reactions: [17][18][19] Anode : Al 7AlCl 4Al Cl 3e 4 2 7…”
mentioning
confidence: 99%